Development of tail rotor power analysis model with feasibility study of electrical tail rotor. - Subramanian, Nithya (Cranfield University, 2016)
In recent years, there has been significant work undertaken by the aviation industry to increase the overall rotorcraft performance, and eventually, eliminate leak prone hydraulic fluids and to reduce CO₂ emissions. Even though a mechanical-gearbox-driven tail rotor has been extensively used in several applications, it comes at the expense of high life cost of the gearbox and shaft gear mechanism. This thesis concentrates on the developing a model to analyse the power requirement for the tail rotor drive and feasibility investigation of an electrical tail rotor to substitute the shaft geared system and the conventional tail rotor power transmission gearbox. A case study is conducted on the Sikosky UH-60A rotorcraft to assess the conventional tail rotor power requirement and Electrical systems. A mathematical model based on Rankine Froude’s momentum theory is created to analyse the power required to drive the anti-torque system, which could be adapted to any conventional drive train (with the main rotor and a tail rotor) rotorcraft. A mission profile and trajectory are created and implemented into Excel based mathematical model. The challenges in implementing electrical drivetrain (electrical generation, energy conversion and electric transmission) are briefly discussed in this thesis. Electrical load analysis database is generated to find the electrical load of the generator for the entire flight phases and utilised to up-scaled the generator to compensate the new load from Electrical tail rotor. The electrical powertrain system is designed with a Brushless DC motor attached to the tail rotor and the generator and the battery for redundancy purposes. The research thesis develops an understanding of current electric motor and battery technology to create a novel design of electric tail drive that increases the reliability of the helicopter system.
Keywords: Electric powered tail rotor; power required to drive tail rotor; electrical load analysis; electric tail drive; 'more-electric' rotorcraft; Sikorsky UH-60A; electrical system